IMPLEMENTATION OF THE SINEACE QUALITY MODELFOR PROFESIONAL CAREERS - Hidalgo Tupia, Manuel Alberto (2015)
In this article, the result of research concluded: “Ele-ments of the System for Quality Management for the Graduate School of the Faculty of Accounting Scien-ces in framework of the Quality model of CONEAU”, we discuss the applicative implications emerging from the SINEACE Quality Model implementation (CONEAU), compared with traditionally managed careers by the Professional Academic Schools and Faculties of Peruvian universities.Likewise we present the principles and foundations, the requirements for its implementation, the impact on management and regulation in the Academic Units, which must go through a reengineering process.Moreover, we discuss the specific implications on the implementation process of the quality system manage-ment in the academic units of the Peruvian university.